(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
This article analyzes the influence of the United States on the Islamic Republic of Iran and Central Asia. It also predicts US-Iran and Central Asia relations in the near future through event analysis, content analysis, and cognitive mapping methods.